Охорона та організація археологічних експедицій в Ольвії у перші роки роботи заповідника (за матеріалами Наукового архіву Інституту археології НАН України) - Станиціна, Г.О. (Археологія, 2001)
Публікація про охоронні заходи та археологічні експедиції на території давньогрецького поселення Ольвія на березі Бузького лиману біля с. Парутине Очаківського р-ну Миколаївської обл. у перші роки створення та становлення Ольвійського заповідника. Використано унікальні архівні документи, які раніше не публікувались. На правом берегу Бугского лимана возле с. Парутино Очаковского р-на Николаевской обл. находятся остатки древнегреческого города Ольвия и его некрополя. После прекращения археологических исследований в 1915г. началось хищническое разграбление Ольвии как местными крестьянами, растаскивавшими древние кладки, так и разного рода кладоискателями. Учитывая большое культурно-историческое значение Ольвии, Совет Народных Комиссаров УССР принял ряд Постановлений, направленных на охрану памятника (1921, 1924). На должность ученого хранителя Ольвии был приглашен заведующий Николаевским историко-археологическим музеем Т. Т. Каминский, принявший действенные меры для охраны и благоустройства заповедника. В 1924 г. возобновились археологические исследования древней Ольвии, в них участвовали представители РАИМК, ВУАК и историко-археологических музеев — Николаевского и Одесского. Возглавлял экспедицию в 1924—1926 гг. академик Б. В. Фармаковский. The remnants of the ancient Greek town of Olbia and its necropolis are situated on the right bank of the Bug estuary, not far from the village of Parutino, (Ochakov district, Mykolaiv region). The cessation of the archaeological investigations in 1915 caused the destructive robbery of Olbia by the local peasants, removing part by part the ancient masonries as well as by different hoards—seekers. Taking into account the big cultural and historical meaning of Olbia Soviet of People’s Commissars of the Ukrainian SSR adopted several resolutions directed at monument protection (1921–1924). The post of a scientist-curator of Olbia was occupied by the head of the Mykolaiv historical-archaeological museum, F. T. Kaminskiy, who took effective measures for the safety and improvement of the preserve. In 1924, archaeological investigations of the ancient Olbia renewed. The representatives from the Russian Academy of History of Material Culture, the All-Ukrainian Archaeological Comity, Mykolaiv, and Odesa historico-archaeological museums took part in these investigations. B. V. Formakovskiy headed the expedition of 1924–1926.